Strategi Kebijakan Dalam Penerbitan Sertifikat Tanah Di Kecamatan Rupitkabupaten Musi Rawas Utara - Ardes Candra; Hartawan Hartawan.; Muhammad Dimas Risqi (Universitas Muhammadiyah Lampung, 2022)
ABSTRACTAbstract: Issuance of land certificates is carried out symbolically and how the strategy is carried out by the government, especially the Land Agency of North Musi Rawas Regency in issuing the land certificate. The research method in this study used a qualitative descriptive. Where the data sources are taken from observations, interviews, and documentation. The results of this study are that the strategy of the BPN of Musi Rawas Utara Regency in issuing land certificates, namely firstly planning activities by socializing to the Rupit sub-district, related hamlet heads and the community who will get the certificate and determining the Pendaftaran Tanah Sistematis Lengkap (PTSL) program. Second, the preparation and determination of the PTSL adjudication committee and task force, outreach to the community. Third, collection and research of physical and juridical data, Announcement of physical and juridical data and their ratification, Confirmation, conversion, recognition of rights or granting of rights, Bookkeeping of rights, Issuance of land rights certificates, Documentation, and results of activities, and Reporting. Keyword: Strategy, Policy, Land Certificate, National Program ABSTRAKAbstrak : Penerbitan sertifikat tanah dilakukan tidak hanya simbolis saja, namun juga bagaimana strategi yang dilakukan oleh pemerintah khususnya Badan Pertanahan Kabupaten Musi Rawas Utara dalam menerbitkan sertifikat tanah tersebut. Metode penelitian dalam penelitian ini menggunakan diskriptif kualitatif. Dimana pengambilan sumber data dari observasi, wawancara, dan dokumentasi. Hasil dari penelitian ini bahwa strategi BPN Kabupaten Musi Rawas Utara dalam penerbitan sertifikat tanah, yakni pertama perencanaan kegiatan dengan melakukan sosialisasi kepada pihak kecamatan rupit, kepala dusun yang terkait dan masyarakat yang akan mendapatkan sertifikat tanah dan penetapan lokasi yang dimasukkan dalam program Pendaftaran Tanah Sistematis Lengkap (PTSL). Kedua, persiapan pembentukan dan penetapan panitia ajudikasi PTSL dan satuan tugas, penyuluhan kepada masyarakat. Ketiga, pengumpulan dan penelitian data fisik dan data yuridis, Pengumuman data fisik dan data yuridis serta pengesahannya, Penegasan, konversi, pengakuan hak atau pemberian hak, Pembukuan hak, Penerbitan sertifikat hak atas tanah, Pendokumentasian dan penyerahan hasil kegiatan, dan Pelaporan. Kata Kunci : Strategi, Kebijakan, Sertifikat Tanah, Program Nasional